Evaluasi Sistem Informasi Aktiva Tetap pada PT TMS - Imelda Suardi; Henny Hendarti (Bina Nusantara University, 2013)
The purpose of this study is to evaluate and assess how well the information system of fixed assets implemented by PT TMS (including general control and application control) in minimizing the current risks through the implemented controls. The methodology used is literature study by collecting data from a variety of books related to the topic and field research, such as observation, interviews, and questionnaires. Results of the evaluation are risks that exist in the system presented in the form of matrix of risk and control which consist of problem findings, potential risks (impact and likelihood) and the reliability of existing control (design and effectiveness). The general control applied by the company is found quite well, but the application control still needs improvement.